2010
DOI: 10.1177/0963662510387759
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting stories about public scientific controversies: Effects of news convergence and divergence on scientists’ credibility

Abstract: Surveys suggest that approximately one third of news consumers have encountered conflicting reports of the same information. News coverage of science is especially prone to conflict, but how news consumers perceive this situation is currently unknown. College students (N = 242) participated in a lab experiment where they were exposed to news coverage about one of two scientific controversies in the United States: dioxin in sewage sludge or the reintroduction of gray wolves to populated areas. Participants rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 48 publications
3
69
0
Order By: Relevance
“…For example, Arora and Arora (2006) examined the effects of two-sided health booklets and demonstrated that these non-news sources enhanced attitudes toward the advocated health behaviors. Jensen and Hurley (2012) explored responses to news articles with conflicting views about dioxin regulation and wolf reintroduction policies; when reading two articles with conflicting views as opposed to a single one-sided article, people expressed greater uncertainty. For an environmental issue, Corbett and Durfee (2004) showed that participants exposed to news with conflicting perspectives, within a broader context, generated significantly higher certainty ratings than those without.…”
Section: Audience Responses To Two-sided Media Coveragementioning
confidence: 99%
“…For example, Arora and Arora (2006) examined the effects of two-sided health booklets and demonstrated that these non-news sources enhanced attitudes toward the advocated health behaviors. Jensen and Hurley (2012) explored responses to news articles with conflicting views about dioxin regulation and wolf reintroduction policies; when reading two articles with conflicting views as opposed to a single one-sided article, people expressed greater uncertainty. For an environmental issue, Corbett and Durfee (2004) showed that participants exposed to news with conflicting perspectives, within a broader context, generated significantly higher certainty ratings than those without.…”
Section: Audience Responses To Two-sided Media Coveragementioning
confidence: 99%
“…Participants were randomly assigned either to a no-blog control or two-blog treatment (one positive and one negative blog featuring opposing views about the vaccine). Similarly, Jensen and Hurley (2012), in a study on the effects of news coverage of two scientific controversies, dioxin regulation and wolf reintroduction, randomly assigned participants to view either two news stories that were consistent with one another on the issue (convergent condition), two stories that conflicted (divergent condition), or one story plus a filler article (control condition). They found that exposure to conflicting stories had effects on perceived uncertainty and scientists’ perceived credibility, but the pattern of effects varied by controversial issue.…”
Section: Contradictory Information: Conceptualizations and Evidence Fmentioning
confidence: 99%
“…Both quantitative and qualitative studies have found that people perceive conflict about these and other topics (Carpenter, Elstad, Blalock, & DeVellis, 2014; Vardeman & Aldoory, 2008), which may drive them to seek more information (Weeks, Friedenberg, Southwell, & Slater, 2012) and influence their behavior decisions (Gibson et al, 2015). Yet few studies have explicitly assessed media exposure to contradictory information (Nagler, 2014; Nagler & Hornik, 2012; Tan, Lee, & Bigman, 2015), and research examining the effects of such exposure is limited (Chang, 2013, 2015; Dixon & Clarke, 2012; Jensen & Hurley, 2012; Nan & Daily, 2015). Health and scientific controversies are increasingly prominent in the media.…”
mentioning
confidence: 99%
“…Paradoxically, there is a general perception among the experts that the more information society has, the more misinformed people are. In recent years, there has been a clear increase of theories, thoughts and ideologies which are based on falsehoods and can be considered potentially dangerous to public health: pseudosciences (Jensen & Hurley, 2012).…”
Section: Introductionmentioning
confidence: 99%